Galaxies and the intergalactic medium: evolutionary interrelations - Shustov, B. M. (Одеські астрономічні публікації, 2017)
During their life galaxies exchange in matter and energy with the intergalactic medium (IGM). This complex process is a most important factor in galactic evolution as well in evolution of the IGM. In this paper recent progress in the IGM studies and mechanisms of mass gain and mass loss from galaxies are briefly reviewed. Using a model of chemo-dynamical evolution of galaxies I discuss enrichment of the IGM with metals and origin of the radial gradients of chemical composition in disk galaxies as possible consequence of heavy elements loss. The general conclusion is simple: many problems remain unsolved but we are under way to understanding of consistent evolution of galaxies - IGM system.